The Effect Injection Width and Temperature-Offset Compensation of Magnetotransistor - Chana Leepattarapongpan; Toempong Phetchakul; Naritchaphan Penpondee; Puttapon Pengpad; Arckom Srihapat; Wutthinan Jeamsaksiri; Charndet Hruanun; Amporn Poyai (My University, 2011)
This paper presents effect of injection witdh on Magnetotransistor. Emitter area was confined by LOCOS and the injection window size was varied from 4, 5 to 10 microns. With bias current of 3 mA the window size 4 micron gives best sensitivity at 10 mV/T. Measument linearity is 0.1% full scale. voltage gain of 10 was used for minimizing temperature coefficient to be around 7.9 mV/°C measured from 25 to 125 °C. Temperature coefficient divided by sensitivity give us a relative temperature sensitivity of 7.9% T/°C. Second magnetic sensor device has been used for temperature compensation. The second device was config as magnetic field immune then it was used as a temperature offset voltage reference. The added module reduces overall temperature sensitivy down to 0.3% T/°C.
Keywords: Linearity; Temperature coefficient; Biasing; Magnetic Field Sensors Techniques